Magnitude and pattern of birth defect babies at Bhopal district early intervention center under RBSK’s 4Ds approach: an observational study - Bhatia, Padma; Sawlani, Harshima; Shinde, Mohan; Tarachandani, Rajesh (International Journal Of Community Medicine And Public Health, 2019)
Background: As per World Health Organization (WHO) congenital anomalies are also known as birth defects, congenital disorders or congenital malformations. Most common and severe congenital anomalies are congenital heart diseases, neural tube defect and Down’s syndrome. No data on the magnitude of congenital anomalies is available in India. Thus, the study aims to determine the magnitude and pattern of babies with birth defect reporting at District Early Intervention Center, Bhopal in children aged 0 to 6 years. Methods: This was an observational study conducted at DEIC, Bhopal under Rashtriya Bal Swasthya Karyakram services, over a period of one year. Children between 0 to 6 years visiting the center and belonging to Bhopal district were included in the study. Data entry was by Microsoft Excel and analysis was by Epi info. Results: 2891 children were registered for the study out of affected children 18.7% of them were diagnosed with Developmental delays while birth defect was observed in 4.3% cases. Of the birth defect cases majority i.e. 37.7% had congenital heart disease and 16.7% had congenital hearing loss. No case of retinopathy of prematurity was registered. Conclusions: The study also helps to know the magnitude and pattern of congenital anomalies. Any effective health intervention will reduce both direct costs and out-of-pocket expenditure.